STRATEGI PENGEMBANGAN KETERAMPILAN BERBAHASA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Aminah, Siti; Cici Elisabeth Sitanggang; Dini Alya Firda; Maudy Aprilia; Silvina Noviyanti; Ahmad Syarif (STKIP Subang, 2026)
Language skills are essential foundational abilities for elementary school students; however, low proficiency levels particularly in reading and writing are still observed due to the limited variety of learning strategies employed. This study aims to analyze strategies for developing language skills in elementary school students through a literature review. The method used is a Systematic Literature Review (SLR) by analyzing scientific articles using the PRISMA flowchart. The results show that learning strategies can be categorized into active learning, media- and technology-based learning, collaborative learning, and literacy-based learning. There is no single strategy that is universally the most effective; however, the integration of these various strategies has proven to be more effective in improving language skills as well as student motivation and participation.